Estudo hidrológico da bacia hidrográfica do Rio Jundiaí-RN visando a implantação de bacia experimental e a atenuação de cheias pela barragem Tabatinga - Troncoso, Raquel Ferreira (2012)
The management of water resources in the river basin level, as it defines the Law nº 9433/97, requires the effective knowledge of the processes of hydrological basin, resulting from studies based on consistent series of hydrological data that reflect the characteristics of the basin. In this context, the objective of this work was to develop the modeling of catchment basin of the river Jundiaí - RN and carry out the study of attenuation of a flood of the dam Tabatinga, by means of a monitoring project of hydrological data and climatology of the basin, with a view to promoting the development of research activities by applying methodologies unified and appropriate for the assessment of hydrological studies in the transition region of the semiarid and the forest zone on the coast of Rio Grande do Norte. For the study of the hydrological characteristics of the basin was conducted the automatic design of the basin of the river Jundiaí, with the aid of programs of geoprocessing, was adopted a hydrological model daily, the NRCS, which is a model determined and concentrated. For the use of this model was necessary to determine some parameters that are used in this model, as the Curve Number. Having in mind that this is the first study that is being conducted in the basin with the employment of this model, it was made sensitivity analysis of the results of this model from the adoption of different values of CN, situated within a range appropriate to the conditions of use, occupation and the nature of the soil of this basin. As the objective of this study was also developing a simulation model of the operation of the Tabatinga dam and with this flood control caused in the city of Macaíba, it was developed a mathematical model of fluid balance, developed to be used in Microsoft Excel. The simulation was conducted in two phases: the first step was promoted the water balance daily that allowed the analysis of the sensitivity of the model in relation to the volume of waiting, as well as the determination of the period of greatest discharges daily averages. From this point, it was assumed for the second stage, which was in the determination of the hydrograph of discharges effluent slots, that was determined by means of the fluid balance time, on the basis of the discharges effluents generated by a mathematical equation whose parameters were adjusted according to the hydrograph daily. Through the analyzes it was realized that the dam Tabatinga only has how to carry out the attenuation of floods through the regularization of the volume of waiting, with this there is a loss of approximately 56.5% on storage capacity of this dam, because for causing the attenuation effect of filled the shell of this dam has to remain more than 5m below the level of the sill, representing at least 50.582.927m3. The results obtained with the modeling represents a first step in the direction of improving the level of hydrological information about the behavior of the basins of the semiarid. In order to monitor quantitatively the hydrographic basin of the river Jundiaí will be necessary to install a rain gauge register, next to the Tabatinga dam and a pressure transducer, for regular measurements of flow in the reservoir of the dam. The climatological data will be collected in full automatic weather station installed in Agricultural School Jundiaí